EVALUASI KEBIJAKAN PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KECAMATAN SEMARANG SELATAN (STUDI KASUS PERATURAN DAERAH KOTA SEMARANG NOMOR 11 TAHUN 2000) - Eka Yuli Trisnawati; Susi Sulandari; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Five Feet traders or a street vendor is abbreviated term for merchandise vendors using carts. Along with the growth of street vendors, emerging issues, among others, is pollution, which is not appropriate spatial and causing traffic jams. To organize street vendors, Semarang City Government issued Local Regulation No. 11 Year 2000 concerning Regulation and Development Street Vendors. This study aims to provide an explanation of the policy-setting and coaching vendors in the District of South Semarang.The research was conducted using Dunn's theory of policy evaluation with several factors, namely effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. The study was designed and analyzed qualitatively descriptive. While the technique of data collection is done by the study of literature, documentation, observation and in-depth interviews with a number of informants.The results of this study indicate that the policy setting and coaching vendors in the District of South Semarang still unwell. It is seen from the many street vendors who violate the rules, PKL complaints regarding the facilities provided by the local government and calls socialization problems that have not performed optimally.The conclusion that can be derived that the policy setting and coaching vendors in the District of South Semarang still not good. Therefore the need for socialization and steady appeal to street vendors. Awareness and participation of traders to comply with the rules is also needed in addition to that required cooperation between vendors, officials and the community for the success of the policy.